2002
DOI: 10.1002/glia.10043
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes from human donors differ in resistance to herpes simplex virus 1 (HSV‐1)

Abstract: Primary cultures of human oligodendrocytes (HOLs) were established from six different donors. Differences in resistance to infection with herpes simplex virus 1 (HSV-1) were determined between the primary cultures of HOL in tissue culture infective dose 50 (TCID 50 ), indirect immunofluoresence (IF), and serial electron microscopy (EM) studies. Virus production at different multiplicities of infection (MOIs) indicated that differences in HSV-1 replication were statistically significant and MOIdependent. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Moreover, in that study, demyelination was followed by remyelination, although it was incomplete and the presence of scars was observed. As in studies with experimental animals, resistance to HSV-1 varies between primary cultures of human OLs and is donor-dependent [ 115 ]. Susceptibility to HSV-1 encephalitis may be caused at least partly by mutations in Toll-like receptors that decrease the intrinsic resistance of CNS cells (neurons and OLs in particular) to HSV-1 infection [ 116 , 117 ].…”
Section: Hsv-1 and Demyelinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in that study, demyelination was followed by remyelination, although it was incomplete and the presence of scars was observed. As in studies with experimental animals, resistance to HSV-1 varies between primary cultures of human OLs and is donor-dependent [ 115 ]. Susceptibility to HSV-1 encephalitis may be caused at least partly by mutations in Toll-like receptors that decrease the intrinsic resistance of CNS cells (neurons and OLs in particular) to HSV-1 infection [ 116 , 117 ].…”
Section: Hsv-1 and Demyelinationmentioning
confidence: 99%
“…For instance, when a recombinant HSV-1 constitutively expressing interleukin-2 (IL-2) was inoculated into mice, it provoked CNS demyelination and optic neuropathy, whereas infection with recombinant viruses expressing IL-4, gamma interferon, IL-12p35, IL-12p40, or IL-12p70 did not induce this effect [ 131 ]. On the other hand, donor-dependent differences in resistance to infection with HSV-1 were established in primary cultures of human OLs [ 115 ].…”
Section: Hsv-1 and Demyelinationmentioning
confidence: 99%
“…Glial cells display genetically determined individual differences to virus infections [112] and are infected by a large number of viruses (for review [113,114]). Especially interesting in this regard is the human herpes virus-6 (HHV-6) and the JC virus (JCV).…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…44 Consistent with this observation and the results reported here, recent experimental studies have shown that human oligodendrocytelike cells are highly susceptible to HSV-1 infection, 45 and that differences in virus-host cell interactions, and hence HSV-1 susceptibility, are probably genetically determined. 46 Interestingly, another member of the Herpesviridae family, human herpesvirus 6 , has also been associated with MS. 47 In summary, our study suggests that sequence variants in a 16.6 kb block spanning intron 1 to intron 2 of PVRL2 may influence the severity of MS in a subset of patients. It is currently unknown whether these variants, or others in LD with them, alter the functionality of the viral receptor region, or affect gene splicing.…”
Section: Discussionmentioning
confidence: 99%